MENINGKATKAN PENGUASAAN VOCABULARY BAHASA INGGRIS DENGAN MENGGUNAKAN MEDIA WORDWALL SISWA KELAS VII MTs. GUPPI KRESNOMULYO - DWI HARTATININGSIH (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2022)
Some problems in mastering vocabulary in students are very diverse, ranging from errors in spelling, pronunciation, and choosing the right words in writing and speaking. This study aims to analyze the increase in vocabulary mastery related to pronouns: subjective, objective and possessive adjectives in grade VII MTs students. through the use of wordwall learning media. This research is classroom action research. The subjects of this study were 24 students of class VII, with details of 10 boys and 14 girls. Data collection techniques using tests and non-tests. The results of the data analysis showed that the average score of the students' vocabulary test in the first cycle was 66.00 and the average value of the students' vocabulary test in the second cycle was 81.00. Cycle II has increased by 15.00. So, student learning outcomes on vocabulary mastery related to pronouns: subjective, objective and possessive adjectives through the use of wordwall media in grade VII MTs students increased. The research implication is that English teachers are expected to use wordwall learning media because it can improve vocabulary mastery related to pronouns: subject, object and possessive. ABSTRAKBeberapa permasalahan dalam penguasaan vocabulary pada siswa sangatlah beragam mulai dari kesalahan pada pengejaan, pengucapan, dan pemilihan kata yang tepat dalam menulis maupun berbicara. Penelitian ini bertujuan untuk menganalisis peningkatan penguasaan vocabulary terkait pronouns:subjective, objective dan possessive adjective pada siswa kelas VII MTs. melalui penggunaan media pembelajaran wordwall. Penelitian ini adalah penelitian tindakan kelas. Subjek penelitian ini adalah siswa kelas VII berjumlah 24 orang dengan rincian 10 orang putra dan dan 14 orang putri. Teknik pengumpulan data menggunakan tes dan nontes. Hasil analisis data nilai rata-rata tes vocabulary siswa pada siklus I yaitu sebesar 66,00 dan nilai rata-rata tes vocabulary siswa pada siklus II yaitu sebesar 81,00. Siklus II mengalami peningkatan sebesar 15,00. Jadi, hasil belajar siswa pada penguasaan vocabulary terkait pronouns:subjective, objective dan possessive adjective melalui penggunaan media wordwall pada siswa kelas VII MTs meningkat. Implikasi penelitian diharapkan guru bahasa Inggris untuk menggunakan media pembelajaran wordwall karena dapat meningkatkan penguasaan vocabulary terkait pronouns:subject, object dan possessive .